Diversity of fish otoliths from the Gulf of Mexico and the Caribbean Sea: Report on the first digital collection of fish otoliths (Actinopterygii) from the Atlantic region of Mexico - Maribel Badillo Alemán; Ariana Solís Gómez; Alfredo Gallardo Torres; Eduardo Pacheco Gongora; Xavier Chiappa-Carrara (Acta Ichthyologica et Piscatoria)
The Otolith Collection of Fishes from the Gulf of Mexico and Caribbean Sea was created with the objective to conserve and illustrate the diversity of these structures from species living in the Gulf of Mexico, the Caribbean Sea, and the freshwater and brackish systems of the Yucatan Peninsula, incorporating morphological descriptions and morphometric data. Otoliths, non-skeletal calcareous structures that develop in the inner ear of fish, are essential for balance and hearing. They have become pivotal tools for age and growth determination, population analysis, and ecological, trophic, and archaeological studies due to their resistance to degradation and the extensive information they provide about the environment and physiology of fish. The collection now includes otoliths from 214 species, representing 67 families, obtained through sampling campaigns and collaborations with local fishermen. The otoliths are extracted using techniques that ensure the integrity of the structures for later preservation. High-resolution images were obtained using optical and scanning electron microscopy, and these images are stored in an online database. This database facilitates research and teaching by providing public access to digital specimens and associated data. In addition to fostering academic development, this collection represents a significant step towards the creation of a national platform for otolith data analysis, aligned with international efforts to digitize biological collections. Despite the financial and logistical challenges involved in building and maintaining biological collections, this collection demonstrates its value as an essential resource for taxonomic, systematic, and ecological studies, as well as for biodiversity education and awareness. The online availability of the collection not only facilitates access to data but also promotes innovation and international collaboration in the study of fishes and their habitats.